Bois-de-Riquet (Lézignan-la-Cèbe, Hérault): A late Early Pleistocene archeological occurrence in southern France. (30th January 2016) - Bourguignon, Laurence; Crochet, Jean-Yves; Capdevila, Ramon; Ivorra, Jérôme; Antoine, Pierre-Olivier; Agustí, Jordi; Barsky, Deborah; Blain, Hugues-Alexandre; Boulbes, Nicolas; Bruxelles, Laurent; Claude, Julien; Cochard, David; et al.
Abstract: The Bois-de-Riquet archeological site (Lézignan-la-Cèbe, Hérault, France) provides significant paleontological and archeological data about the first occupations of Western Europe. Although only partially excavated, the site has already yielded an exceptionally rich paleontological assemblage as well as some stone artefacts. The archeostratigraphical unit "US2" is encased within a basalt flowstone radiometrically dated to 1.57 Ma. The sedimentary infill has preserved large and small mammal fossils, as well as coprolites. Biochronological interpretations suggest an age of around 1.3–1.1 Ma for the accumulation. A few basalt artefacts were exhumed alongside the fossil bones. Interpretation of the lithics has required the elaboration of a strict selection protocol based upon extensive knapping experiments with local basalt. This paper presents results from the interdisciplinary study of the Bois-de-Riquet site in the aim of contextualizing these discoveries. The microstratigraphical analysis of the deposits is presented with recent geological interpretations in order to contribute a better understanding of the main features of this assemblage, and its remarkable preservation within the thermal and textural boundary between a basalt flowstone's base and its entablature.